Plasmon‐Enhanced Fluorescent Sensor based on Aggregation‐Induced Emission for the Study of Protein Conformational Transformation. (20th January 2019) - Cui, Yanyun; Yuan, Chang; Tan, Hongwei; Zhang, Zhanbin; Jia, Yijing; Na, Na; Ouyang, Jin
Abstract: The alteration in protein conformation not only affects the performance of its biological functions, but also leads to a variety of protein‐mediated diseases. Developing a sensitive strategy for protein detection and monitoring its conformation changes is of great significance for the diagnosis and treatment of protein conformation diseases. Herein, a plasmon‐enhanced fluorescence (PEF) sensor is developed, based on an aggregation‐induced emission (AIE) molecule to monitor conformational changes in protein, using prion protein as a model. Three anthracene derivatives with AIE characteristics are synthesized and a water‐miscible sulfonate salt of 9, 10‐bis(2‐(6‐sulfonaphthalen‐2‐yl)vinyl)anthracene (BSNVA) is selected to construct the PEF–AIE sensor. The sensor is nearly non‐emissive when it is mixed with cellular prion protein while emits fluorescence when mixed with disease‐associated prion protein (PrP Sc ). The kinetic process of conformational conversion can be monitored through the fluorescence changes of the PEF–AIE sensor. By right of the amplified fluorescence signal, this PEF–AIE sensor can achieve a detection limit 10 pM lower than the traditional AIE probe and exhibit a good performance in human serum sample. Furthermore, molecular docking simulations suggest that BSNVA tends to dock in the β‐sheet structure of PrP by hydrophobic interaction between BSNVA and the exposed hydrophobic residues. Abstract : 9, 10‐bis[2‐(6‐sulfonatopropoxyl)naphthylethenyl]anthracene (BSNVA) molecules with aggregation‐induced emission performance are introduced into a plasmon‐enhanced fluorescence system to build a hybrid sensor, and the fluorescence intensity of BSNVA is enhanced by the core–shell gold nanocube. Based on the specific recognition of proteins by the aptamer and the interaction between the protein and BSNVA, the sensor is applied to turn‐on detection of prion proteins and monitor its conformational transformation.